Moment inequality, central limit theorem, and the invariance principle for linearly positive quadrant dependent random fields - Mukhamedov, Abdurakhman (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 519.21We obtain the moment inequality by considering the central limit theorem for the sums of linearly positive quadrant dependent random fields when the covariance satisfies certain conditions. Applying this moment inequality, we prove the invariance principle.